INTEGRATING ONLINE PLATFORMS AND APPLICATIONS INTO ESL CLASSROOMS: ENHANCING ACADEMIC RIGOR AND EFFECTIVENESS - Saydibragimova Yulduzxon (Modern American Journals, 2025)
This article examines how the integration of online platforms and educational applications in English as a Second Language (ESL) classrooms contributes to heightened academic rigor and instructional effectiveness. Drawing on empirical studies, meta-analyses, and theoretical frameworks, it explores increased student engagement, personalized and self-regulated learning, the affordances of blended and collaborative learning models, and considerations of equity. Implications for practice and areas for further research are discussed.
Keywords: Digital platforms, effective learning, interactive tools, metacognitive skills, cross-cultural communication, blended learning